Educating Data Scientists and Data Literate Citizens for a New Generation of Data - Wise, Alyssa Friend (The Journal of the learning sciences, 2020)
This article discusses how each of the papers in this special issue explored some combination of subject, audience, and data scientist perspectives with an eye toward helping students situate their relationship to data. Specifically, within the data scientist perspective, the papers examined a variety of ways in which students can relate to data through involvement in their collection/generation, storage, transformation, interpretation and representation, and the ways in which these data scientist perspectives can productively be combined with the perspectives of data subject and audience.